REMOVAL OF COPPER IONS USING ALIQUAT 336/TBP BASED SUPPORTED LIQUID MEMBRANE - Baghdad Medjahed; MOHAMED A. DIDI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2014)
The sorption of copper (II) present in an aqueous media using a supported liquid membrane (SLM) by chloride tri-N-octylmethylammonium (Aliquat 336) and Tri-n-butylphosphate (TBP) from molar ratio 1:1, with polytetrafluoroethylene (PTFE) as a membrane support was studied. The effects of various parameters as initial pH, KSCN concentration and ammonium acetate concentration on the extraction yield were carried out. By a calculation program using CHEAQS V. L20.1, the determination of the percentages of the present species before and after extraction were given, in aqueous medium and on the membrane to be able to determine the relation between the nature of the extracted species and the extraction yield. The 23 factorial design achieve the best conditions of recovery procedure. The recovery of copper (II) is almost quantitative (94 %), in one step.